Manajemen Pengumpulan dan Pendistribusian Zakat di Badan Amil Zakat Nasional (BAZNAS) Kota Pematangsiantar - Gita Nurul Fitri Damanik; Imsar Imsar (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
The management or control of zakat distribution is very important so that the zakat funds received by Amil can be routed and targeted in accordance with Sharia principles. This study attempts to analyze the management of zakat in BAZNAS Pematangsiantar City, which includes the planning, organization, implementation / mobilization and monitoring of zakat distribution. This type of research is field research with a qualitative descriptive approach. The results showed that BAZNAS in Pematangsiantar City acts as a distribution manager in accordance with management theory and there are several supporting and inhibiting factors in zakat distribution.